Programmatic innovations that accord with the retention of women in STEM careers - Balasubramanian, Rama; Findley-Van Nostrand, Danielle; Fleenor, Matthew C. (Frontiers in Education, 2023)
Gender representation in the physical sciences remains inequitable and continues to lag behind other fields. Even though there exists adequate documentation regarding programmatic postures, difficulties persist within the physics discipline. In this paper, we present innovative, programmatic elements over an eight-year period at an undergraduate, liberal arts, physics program. These elements were added in response to the following two questions: “What practices cultivate an increase of physics major numbers in an undergraduate, liberal arts setting?”; and, “What practices facilitate a depth of experience for individual physics graduates?” Some of these innovations accord with published, ‘best practices’ for undergraduate physics programs, while others are novel to the program’s context. Within this eight-year period, alterations are separated into curricular and co-curricular elements. Innovations are introduced in some detail, and data are presented before, during, and after their introduction. While it is currently impossible to say which elements had the greatest impact, the synergistic combination did have a positive effect on the program. Not only did the number of total majors and graduates increase, there was a 200% increase of women degree recipients compared to the previous ten years, which boosted average graduation rates above the national average (30% > 20%). Women were retained within the undergraduate physics major at a higher percentage during this time period when compared to men in the program. Lastly, these women physics majors maintained careers in science advancement fields at a rate of 80+% after ≤ 5 years post- graduation. While this paper presents a singular case study, the purpose is two-fold: a) to validate quantitatively the work of national physics organizations within the context of a liberal arts institution, and b) to suggest that a multi-level approach is most efficacious when considering programmatic innovations.